2018
DOI: 10.3390/w10040508
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Streambank and Artificial Gravel Deposit Erosion for Sediment Replenishment

Abstract: Sediment replenishment by artificial gravel deposits is a measure to increase sediment supply in gravel-bed rivers. Thereby, streambank erosion is the dominant process for gravel entrainment. In this contribution, we quantitatively validate a numerical morphodynamic 2D model and the relevant model approaches to reproduce non-cohesive streambank erosion. Therefore, a calibration and a sensitivity analysis of the relevant model approaches and parameters are carried out based on a reference laboratory experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…River widenings are characterized by a locally increased channel width and resulting local morphological adjustments [40]. Dynamic river widenings are more likely to display a barpool morphology than fully developed braiding, due to their limited spatial extent and the degradational state commonly associated with channelized gravel-bed rivers [29]. This assumption is supported by reports on several dynamic river widenings in Austria and Switzerland [35,41].…”
Section: Effects Of Variable Sediment Supply On Dynamic River Wideningsmentioning
confidence: 96%
See 1 more Smart Citation
“…River widenings are characterized by a locally increased channel width and resulting local morphological adjustments [40]. Dynamic river widenings are more likely to display a barpool morphology than fully developed braiding, due to their limited spatial extent and the degradational state commonly associated with channelized gravel-bed rivers [29]. This assumption is supported by reports on several dynamic river widenings in Austria and Switzerland [35,41].…”
Section: Effects Of Variable Sediment Supply On Dynamic River Wideningsmentioning
confidence: 96%
“…Venditti et al [28], however, described the degradation of alternate bars either by migrating out of the channel or by vertical erosion, resulting in a plane bed. The contrasting behavior was explained with different values of relative submergence of the bar tops and it was concluded that bar emergence will more likely occur, especially if the decrease of sediment supply is accompanied by a reduction of peak flows [29]. This is a realistic scenario for river reaches below storage power plants.…”
Section: Variable Sediment Supply In Channelsmentioning
confidence: 99%
“…The research articles included in this special issue specifically targeted three areas that are key to better understanding streambank erosion and failure, namely, monitoring [8][9][10][11], modeling [12][13][14][15][16][17], and management [18][19][20][21]. As an ensemble, the articles highlight the value of monitoring campaigns to characterize the effect of external drivers (e.g., hydrologic events), the capabilities and limitations of numerical models for predicting the response of the system (e.g., stream restoration design), and the effectiveness of management practices to prevent and mitigate the impacts of streambank erosion and failure.…”
Section: Main Outcomes Of the Special Issuementioning
confidence: 99%
“…Their results show that the model's predictions are highly dependent on the bank physical properties at the sub-reach scale, particularly for the case of soil cohesion and friction angle. Finally, Vonwiller et al [17] validated a 2D hydro-morphodynamic model and performed sensitivity analyses to examine the suitability of various approaches (e.g., gravitational bank collapse) to simulate non-cohesive bank erosion in straight channels and the erosion of artificial gravel deposits.…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation